PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA, DAN KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA ANGGOTA TKBM - Bayu Aji Surya Ningrat; Rahmat Hidayat Kurniawan (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to examine and analyze the influence of organizational culture, work discipline, and K3 on employee performance. The sampling technique used in this study was proportional random sampling and the total sample size was calculated using the slovin technique, which resulted in a total of 90 respondents. The data analysis technique used is multiple linear regression analysis with the help of SPSS version 26. The type of data in this study is questionnaire. Based on the results of the analysis it can be concluded that organizational culture variables partially have a significant effect on the performance of TKBM members, work discipline variables partially have a significant effect on the performance of TKBM members, Occupational Health and Safety (K3) variables partially affect the performance of TKBM members at Berlian Tanjung Perak Terminal Surabaya.